(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In children with acute respiratory tract infections (ARTI), elevations of serum liver enzyme activities are frequently observed in clinical practice. However, epidemiological data particularly in the pediatric population are very limited. The aim of this study was to assess the incidence of hepatic involvement, to identify the viruses and to analyze risk factors in children and adolescents with ARTI in a real-world setting.